Genetic characterization of ESBL producing strains of Klebsiella pneumoniae from Tehran hospitals - Feizabadi, Mohammad Mehdi; Mahamadi-Yeganeh, Samira; Mirsalehian, Akbar; Mirafshar, Seyed-Mohammad; Mahboobi, Mohaddeseh; Nili, Firoozeh; Yadegarinia, Davood (The Journal of Infection in Developing Countries, 2010)
Introduction: This study was conducted to determine the genetic characterization of extended-spectrum beta-lactamase (ESBL) producing strains of Klebsiella pneumoniae isolated from Iranian patients in hospitals in Tehran. Methodology: Antibiotic susceptibility of 104 isolates was determined using the disk diffusion test. The Minimum Inhibitory Concentrations (MICs) of imipenem and meropenem were determined for isolates showing reduced susceptibility to carbapenems. The phenotypic confirmatory test (PCT) was used to screen the isolates for ESBL production. PCR was used to detect blaSHV, blaTEM and blaCTX-M and the amplicons from selected clones were sequenced. Isolates producing ESBLs were analyzed by pulsed-field gel electrophoresis (PFGE). Results: One isolate showed resistance to imipenem (MIC = 16 µg/ml). Resistance to amikacin and ciprofloxacin was 44.2% and 25.0%, respectively. ESBL production was detected in 72.1% (n = 75) of isolates. The prevalence of blaSHV, blaTEM and blaCTX-M genes among the isolates was 55.7% (n = 58), 30.7% (n = 32) and 45.2% (n = 47), respectively. The sequencing revealed the amplicons corresponding to bla (TEM-1, TEM-79, SHV-1, SHV-12, SHV-31, CTX-M-15) genes. While the blaCTX-M-15 is the dominant gene among the Iranian isolates, we detected the blaSHV-31 and blaTEM-79 genes for the first time in the country. PFGE differentiated the 71 ESBL-producing isolates into 62 different genotypes. Clonal dissemination of ESBLs was found in the neonatal intensive care unit and intensive care unit of one hospital. Conclusion: The findings are evidence of the spread of multi-resistant clones of ESBL producers in Tehran hospitals.